Phytochemical Analysis of Endemic Klasea bornmuelleri (Azn.) Greuter & Wagenitz Extracts and Evaluation of Insecticidal and Enzyme Inhibitory Activities - Hana HASSAN AHMED; Ebru DERELLİ TÜFEKÇİ; Ali Rıza TÜFEKÇİ; Bilal ŞAHİN; Ömer Cem KARAKOÇ (ISPEC Journal of Agricultural Sciences)
This study investigates the phytochemical constituents of Klasea bornmuelleri extracts and evaluates their insecticidal and enzyme inhibitory activities. The chemical composition of flower and stem-leaf extracts was analyzed by Gas Chromatography-Mass Spectrometry (GC-MS), revealing significant amounts of fatty acid esters, hydrocarbons, and other secondary metabolites in both extracts. Liquid chromatography-mass spectrometry/mass spectrometry (LC-MS/MS) analysis identified phenolic acids, particularly quinic acid and chlorogenic acid, as the dominant components. The concentrations of these compounds were 3786.19 µg g-1 and 3815.43 µg g-1 for stem-leaf (KBSL) extracts and 2081.38 µg g-1 and 4536.21 µg g-1 for flower (KBF) extracts. The methanol:chloroform (1:1) (KBF-MC and KBSL-MC) extracts demonstrated significant inhibitory activity against tyrosinase, xanthine oxidase, and acetylcholinesterase (AChE) in enzyme inhibition assays. The insecticidal potential of Klasea bornmuelleri was evaluated on Sitophilus granarius for periods of 24, 48, and 72 hours, with no insecticidal activity observed at any time. In trials with Tribolium castaneum, hexane extracts from both flower and stem-leaf parts (KBF-H and KBSL-H) showed no significant insecticidal activity. However, KBSL-MC extracts exhibited a consistent mortality rate of 21.15 ± 4.69% across all time points. The KBF-MC extracts showed slightly higher efficacy with mortality rates of 26.07 ± 7.40% at 24 hours, 28.29 ± 8.53% at 48 hours, and 28.29 ± 8.53% at 72 hours. These findings indicate that the KBF-MC and KBSL-MC extracts derived from the Klasea bornmuelleri plant exhibit significant insecticidal and enzyme inhibitory properties, highlighting their potential as promising agents for the natural product-based control of storage pests and warranting further investigation.